2023
DOI: 10.1021/acs.energyfuels.2c03359
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Asphaltene Deposition and Its Impact on Oil Recovery in Eagle Ford Shale during Miscible and Immiscible CO2 Huff-n-Puff Gas Injection

Abstract: One of the challenges in extracting oil from unconventional resources using hydraulic fracturing and horizontal drilling techniques is the low primary recovery rate, which is caused by the ultra-small permeability of these resources. Consequently, it is essential to investigate gas injection methods to produce the trapped oil in shale formations. However, the injection process can cause asphaltene depositions inside the reservoir, leading to plugging of pores and oil recovery (OR) reduction. There has been lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 125 publications
0
8
0
Order By: Relevance
“…Formation damage as a result of asphaltene deposition in conventional reservoirs has been reported . Asphaltene deposition can cause more serious plugging problems in shale as a result of its nanometer pore sizes. , For example, Shen et al measured the sizes of the asphaltene particle formed during CO 2 injection in the oil sample from the Wolfcamp shale reservoir. They compared asphaltene particle sizes to the pore size of cores and found that pore sizes (3–50 nm) are even smaller than asphaltene particle sizes (30 and 200 nm).…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Formation damage as a result of asphaltene deposition in conventional reservoirs has been reported . Asphaltene deposition can cause more serious plugging problems in shale as a result of its nanometer pore sizes. , For example, Shen et al measured the sizes of the asphaltene particle formed during CO 2 injection in the oil sample from the Wolfcamp shale reservoir. They compared asphaltene particle sizes to the pore size of cores and found that pore sizes (3–50 nm) are even smaller than asphaltene particle sizes (30 and 200 nm).…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Miscibility refers to the ability of substances to form a homogeneous mixture. CO 2 EOR means the dissolution of CO 2 into oil, requiring reservoir pressure exceeding the MMP (Elturki and Imqam, 2023). Achieving miscibility involves multiple contacts due to factors like reservoir conditions and oil composition, rather than first contact.…”
Section: Miscibilitymentioning
confidence: 99%
“…However, the practical applications of CO 2 -EOR do not always achieve the expectations, especially for shale oil extraction. One particularly noteworthy problem is that, though CO 2 injection could extract the light and medium components of shale oil first, and the initial recovery is improved, most of the heavy components still remain in the shale reservoirs, and the total oil recovery is limited. , Due to the recent research learning, there is serious restrictive effect of heavy polar components, such as the asphaltene molecules to the displacement of light and medium components of shale oil in the CO 2 flooding process; further solutions have to be conducted to solve the essential problem. Investigating the mechanisms and the influencing factors to discover clues that overcome the bottleneck problems is important for the development of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…noteworthy problem is that, though CO 2 injection could extract the light and medium components of shale oil first, and the initial recovery is improved, most of the heavy components still remain in the shale reservoirs, and the total oil recovery is limited. 28,29 Due to the recent research learning, 30 there is serious restrictive effect of heavy polar components, such as the asphaltene molecules to the displacement of light and medium components of shale oil in the CO 2 flooding process; further solutions have to be conducted to solve the essential problem.…”
Section: Introductionmentioning
confidence: 99%